Accelerated radial diffusion spectrum imaging using a multi‐echo stimulated echo diffusion sequence. Issue 1 (31st March 2017) - Baete, Steven H.; Boada, Fernando E.
Abstract : Purpose: Diffusion spectrum imaging (DSI) provides us non‐invasively and robustly with anatomical details of brain microstructure. To achieve sufficient angular resolution, DSI requires a large number of q‐space samples, leading to long acquisition times. This need is mitigated here by combining the beneficial properties of Radial q‐space sampling for DSI with a Multi‐Echo Stimulated Echo Sequence (MESTIM). Methods: Full 2D k‐spaces for each of several q‐space samples, along the same radially outward line in q‐space, are acquired in one readout train with one spin and three stimulated echoes. RF flip angles are carefully chosen to distribute spin magnetization over the echoes and the DSI reconstruction is adapted to account for differences in diffusion time among echoes. Results: Individual datasets and bootstrapped reproducibility analysis demonstrate image quality and SNR of the more‐than‐twofold‐accelerated RDSI MESTIM sequence. Orientation distribution functions (ODF) and tractography results benefit from the longer diffusion times of the latter echoes in the echo train. Conclusion: A MESTIM sequence can be used to shorten RDSI acquisition times significantly without loss of image or ODF quality. Further acceleration is possible by combination with simultaneous multi‐slice techniques. Magn Reson Med 79:306–316, 2018. © 2017 International Society for Magnetic Resonance in Medicine.